Karyotype changes in long-term cultured tick cell lines - Kotsarenko, Kateryna (2020)
Tick cell lines are an easy-to-handle system for the study of viral and bacterial infections and other aspects of tick cellular processes. Tick cell cultures are often continuously cultivated, as freezing can affect their viability. However, the long-term cultivation of tick cells can influence their genome stability. In the present study, we investigated karyotype and genome size of tick cell lines. Though 16S rDNA sequencing showed the similarity between Ixodes spp. cell lines at different passages, their karyotypes differed from 2n=28 chromosomes for parental Ixodes spp. ticks, and both increase and decrease in chromosome numbers were observed. For example, the highly passaged Ixodes scapularis cell line ISE18 and Ixodes ricinus cell lines IRE/CTVM19 and IRE/CTVM20 had modal chromosome numbers 48, 23 and 48, respectively. Also, the Ornithodoros moubata cell line OME/CTVM22 had the modal chromosome number 33 instead of 2n=20 chromosomes for Ornithodoros spp. ticks. All studied tick cell lines had a larger genome size in comparison to the genomes of the parental ticks. Thus, highly passaged tick cell lines can be used for research purposes, but possible differences in encoded genetic information and downstream cellular processes, between different cell populations, should be taken into account.